2013
DOI: 10.1187/cbe-12-06-0070
|View full text |Cite
|
Sign up to set email alerts
|

Six Classroom Exercises to Teach Natural Selection to Undergraduate Biology Students

Abstract: Six classroom lessons are presented for teaching undergraduate students in introductory biology courses how natural selection works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
0
23
0
4
Order By: Relevance
“…For example, if an instructor is interested in whether a curriculum component increases students’ knowledge about natural selection, the Conceptual Inventory of Natural Selection (Anderson et al. , 2002) may be appropriate to use as a pre- and posttest (e.g., Kalinowski et al. , 2013).…”
Section: Teaching Versus Education Research Postdoctoral Positionsmentioning
confidence: 99%
“…For example, if an instructor is interested in whether a curriculum component increases students’ knowledge about natural selection, the Conceptual Inventory of Natural Selection (Anderson et al. , 2002) may be appropriate to use as a pre- and posttest (e.g., Kalinowski et al. , 2013).…”
Section: Teaching Versus Education Research Postdoctoral Positionsmentioning
confidence: 99%
“…Student misconceptions regarding evolution are very resistant to instruction (Gregory, 2009), but can be improved with the series of activities and teaching strategies (e.g. Dees, Momsen, Niemi, & Montplaisir, 2014;Kalinowski, Leonard, Andrews, & Litt, 2013;Kampourakis & Zogza, 2008;Nehm and Schonfeld, 2007;Pope, Rounds, & Clarke-Midura, 2017). Nehm and Schonfeld (2007) found that students tend to retain only what is necessary to pass the exam before returning back to their original beliefs about evolution.…”
Section: Knowledge Of Evolutionmentioning
confidence: 99%
“…Andrews et al 2012;Gregory 2008) and may look into peer-reviewed curricula for activities designed to counter misconceptions about evolution (e.g. Andrews et al 2011;Govindan 2018;Kalinowski et al 2013;Meisel 2010).…”
Section: Concept Inventories Can Identify Key Misconceptions Studentsmentioning
confidence: 99%